2019
DOI: 10.1161/circep.119.007573
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Saturated Fat Promotes Arrhythmia by Activating NOX2 (NADPH Oxidase 2)

Abstract: Background: Obesity and diets high in saturated fat increase the risk of arrhythmias and sudden cardiac death. However, the molecular mechanisms are not well understood. We hypothesized that an increase in dietary saturated fat could lead to abnormalities of calcium homeostasis and heart rhythm by a NOX2 (NADPH oxidase 2)-dependent mechanism. Methods: We investigated this hypothesis by feeding mice high-fat diets. In vivo heart rhythm telemetry, optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…Apocynin treatment and the ablation of NOX2 partly normalized superoxide derived EOH, but had no effect on ethidium, suggesting reduced NOX2 activity when compared to reduced NOX4 (which primarily produces H 2 O 2 ). Our results are also in line with previous data showing reduced cardiac NOX2 activity in diabetes and high fat feeding of mice following both the genetic ablation of NOX2 [8,44] and pharmacological treatment with NOX2-inhibitors [8,11].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Apocynin treatment and the ablation of NOX2 partly normalized superoxide derived EOH, but had no effect on ethidium, suggesting reduced NOX2 activity when compared to reduced NOX4 (which primarily produces H 2 O 2 ). Our results are also in line with previous data showing reduced cardiac NOX2 activity in diabetes and high fat feeding of mice following both the genetic ablation of NOX2 [8,44] and pharmacological treatment with NOX2-inhibitors [8,11].…”
Section: Discussionsupporting
confidence: 93%
“…While SHFD induced heart rhythm abnormalities in WT mice, this was absent in NOX2 KO hearts and following apocynin treatment. Additionally, the oxidation of the RYR2 promotes calcium leak and increased calcium sparks, which were also absent in NOX2 KO hearts from mice that were fed a SHFD [44]. Other studies have reported a negative impact of NOX2-derived superoxide following acute exposure to FA load [25] and in other types of heart failure [28].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar to PUFAs, monounsaturated fatty acids (MUFAs), such as oleic acid (the major component of olive oil), also result in better cardiovascular outcomes in comparison to saturated fats [ 26 ]. Consuming foods high in saturated fat increase risk of stroke, CVD, and SCD [ 23 , 27 ]. Trans fats, which are artificial and have been banned in several countries as food ingredients, further increase the risk of adverse cardiovascular events beyond that of saturated fat [ 28 ].…”
Section: Types Of Dietary Fatmentioning
confidence: 99%
“…This substrate can lead to RIRR, as mentioned earlier, and may further cause heterogeneous repolarization of cardiac myocytes, a mechanism of arrhythmic propagation. In fact, we have previously shown via optical mapping that rodents fed a high-saturated-fat diet have significantly greater repolarization heterogeneity and increased action potential duration (APD) than mice fed standard chow [ 27 ]. This could contribute to sustained arrhythmias.…”
Section: Arrhythmogenic Mechanisms Caused By Hfd And/or Obesitymentioning
confidence: 99%